Pseudomonas aeruginosa LptE is crucial for LptD assembly, cell envelope integrity, antibiotic resistance and virulence. Issue 1 (31st December 2018) - Lo Sciuto, Alessandra; Martorana, Alessandra M.; Fernández-Piñar, Regina; Mancone, Carmine; Polissi, Alessandra; Imperi, Francesco
ABSTRACT: Lipopolysaccharide (LPS) is an essential structural component of the outer membrane (OM) of most Gram-negative bacteria. In the model organism Escherichia coli, LPS transport to the OM requires seven essential proteins (LptABCDEFG) that form a continuous bridge across the cell envelope. In Pseudomonas aeruginosa the recently-demonstrated essentiality of LptD and LptH, the P. aeruginosa LptA homologue, confirmed the crucial role of the Lpt system and, thus, of LPS in OM biogenesis in this species. Surprisingly, independent high-throughput transposon mutagenesis studies identified viable P. aeruginosa insertion mutants in the lptE gene, suggesting that it might be dispensable for bacterial growth. To test this hypothesis, we generated an lptE conditional mutant in P. aeruginosa PAO1. LptE depletion only slightly impairs P. aeruginosa growth in vitro . Conversely, LptE is important for cell envelope stability, antibiotic resistance and virulence in an insect model. Interestingly, the maturation and OM localization of LPS is only marginally affected in LptE-depleted cells, while the levels of the OM component LptD are strongly reduced. This suggests that P. aeruginosa LptE might not be directly involved in LPS transport, although it is clearly essential for the maturation and/or stability of LptD. While poor functionality of LptD caused by LptE depletion is somehow tolerated by P. aeruginosa, this has a high cost in terms of cell integrity, drug resistance and virulence, highlighting LptE function(s) as an interesting target to weaken P. aeruginosa defenses and reduce its infectivity.